Kompetensi Guru dalam Perspektif Undang-Undang Menurut Sistem Pendidikan Nasional - Rachmah, Anisah Aulia; Ifadah, Alik; Hisyam Hilmi, Muhamad; Dinal Haq, M. Da'i; Khobir, Abdul; Kamilia, Nadya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study is to assess teacher skills and competencies as referenced in Indonesian national education regulations, specifically Law Number 20 of 2003 and Law Number 14 of 2005. This study employed qualitative methods and utilized desk research. Various studies, regulations, and articles relevant to this topic were analyzed. This research focused on understanding teacher competencies, National Education Standards, and the factors that determine teacher competency. The results indicate that teacher competency is a key element in determining the quality of national education. Law Number 14 of 2005 concerning Teachers and Lecturers states that teachers are required to possess four competencies: pedagogic, personality, social, and professional. The National Education Standards aim to improve the quality and professionalism of teaching. Various government policies, training programs, continuing professional development (PPB), and teacher certification play a crucial role in supporting teacher competency improvement. However, teacher professional development still faces various challenges in the education sector, such as budget constraints, inadequate facilities, and low teacher motivation to improve their quality and competency. The study results show that teacher competencies stipulated in legislation are closely linked to the realization of quality education and the achievement of national education goals. Therefore, optimizing relevant and sustainable professional development requires a synergistic partnership between the government, educational institutions, and teachers.